KEMAMPUAN MENGANALISIS UNSUR INTRINSIK KARYA SASTRA - Yanti, Cita Hikmah; Neisya, Neisya (Jurnal Ilmiah Bina Edukasi, 2021)
This study aims to evaluate the teaching of literary appreciation in improving the ability to analyze the intrinsic elements of a literary work. The object of this research is the 3rd semester students of the English Literature Study Program, Faculty of Teacher Training and Education and Language Sciences at Universitas Bina Darma. This study uses the CAR method (class action research) where this method has 3 cycles. In each cycle, researchers and teachers will evaluate the results of teaching in each cycle to be improved in the next cycle. In this study, the intrinsic elements that will be analyzed by students are the theme, setting, characterizations, plot, point of view, message and style of language. By using the methods and teaching materials that have been prepared in the third cycle, researchers and teachers have been able to significantly improve the ability to analyze the intrinsic elements of a literary work.